Uncertainty in decision-making: A review of the international business literature - Sniazhana Sniazhko (Taylor & Francis Group, 2019)
Uncertainty is a key contextual factor that affects the decision-making of multinational corporations on many types of international operation. However, the variety of ways in which uncertainty has been defined and studied in the international business literature, has contributed to a fragmented view of MNC behavior and of the role of uncertainty in international decision-making. Adopting a broad view of uncertainty, and by means of a systematic review, this paper examines the treatment of uncertainty in international decision-making in the IB literature and identifies directions for future research. The review organizes studies across 13 dimensions of uncertainty and eight approaches to managing it. The paper further identifies five characteristics of individual decision-makers that have been shown to impact their perceptions of uncertainty and their choice of uncertainty management approach. Based on this systematic review, the paper makes three main critical observations about existing research: inconsistency in the conceptualization and measurement of uncertainty, lack of diversity regarding the dimensions of uncertainty included in single studies, and downplaying the role of individual decision-makers. A research agenda is presented that offers suggestions on how future research might address these limitations.